Tinjauan Sosiologi Sastra dalam Novel Hafalan Shalat Delisa Karya Tere Liye dan Relevansinya terhadap Pembelajaran Sastra di SMA - Rita Nilawijaya; Awalludin Awalludin (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
The purpose of this study was to describe the novel building structure, the moral aspects of Tere Liye's Hafalan Shalat Delisa novel, and its relevance to literary learning in high school. The research method used is descriptive qualitative method. The object of this research is the moral aspect. The data source in this study is the novel Hafalan Shalat Delisa by Tere Liye. The technique of collecting data uses library techniques, listening, taking notes, and interviews. Data analysis techniques using dialectical techniques. The results showed that (1) structural analysis resulted in the theme of this novel being unyielding, patient, and steadfast. The flow used is a progressive path. The main character is named Delisa and additional figures are Ummi Salamah, Kak Fatimah, Kak Aisyah, Kak Zahra, Abi Usman, Koh Acan, Ustadz Rahman, Ibu Guru Nur, Sersan Ahmed, Prajurit Smith/Salam, Suster Shopi, Tiur, Umam, and Kak Ubai. The setting in this novel is located in Lhok Nga, the aircraft carrier, and the hospital. The time frame is between 2004 and 2005. The social background includes life habits, traditions, and beliefs in religion; (2) moral aspects in the novel Hafalan Shalat Delisa include honesty, authentic values, responsibility, independence, and realistic and critical morals. Then, (3) the results of this study have relevance to literature learning in high school which is indicated by the existence of material about moral values ​​in novels as part of character education that must be learned by students.